2010
DOI: 10.3109/01443611003605286
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic value of β-human chorionic gonadotropin, progesterone, CA125 in the prediction of abortions

Abstract: This study was conducted to investigate the effectiveness of serum levels of free beta-hCG, progesterone, CA125 and their combined use in the prediction of first trimester abortions. A total of 140 singleton pregnant women between 5 and 13 weeks' gestational age were included as Group I (n = 21) who resulted in abortion including missed abortion, incomplete abortion, complete abortion and inevitable abortion; Group II (n = 129) included normal pregnancies. When using the free beta-hCG level of <20 ng/ml as a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
22
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 21 publications
4
22
0
2
Order By: Relevance
“…When a value of 15 ng/mL was set as the cutoff point for progesterone [21] , 91 patients had < 15 ng/mL and 82 had ≥ 15 ng/mL progesterone level. Median age of patients with < 15 ng/mL progesterone level and ≥ 15 ng/mL progesterone level was 28 (6) and 28.5 (6) years, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…When a value of 15 ng/mL was set as the cutoff point for progesterone [21] , 91 patients had < 15 ng/mL and 82 had ≥ 15 ng/mL progesterone level. Median age of patients with < 15 ng/mL progesterone level and ≥ 15 ng/mL progesterone level was 28 (6) and 28.5 (6) years, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Several potential ultrasonographic and endocrinologic markers have been previously investigated for predicting pregnancy loss [2,14,19,21,24] . However, a novel ultrasonographic marker called " decidual thickness " has been recommended to discriminate women with pregnancy loss from those with healthy pregnancy [24] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, although either progesterone or b-HCG measurements can be used for prediction of abortion the concern on cost of the laboratory test is required. Based on the mentioned facts, it is suggested that single progesterone test is more proper due to lower cost and easier availability [7]. As a summary, this letter raises an important laboratory concern on using progesterone and beta human chorionic gonadotropin measurements in predicting the natural course of threatened miscarriage.…”
mentioning
confidence: 99%